A phase 2 trial of GVHD prophylaxis with PTCy, sirolimus, and MMF after peripheral blood haploidentical transplantation - Bejanyan, Nelli (Blood Adv, 2021)
The introduction of posttransplant cyclophosphamide (PTCy) made performing allogeneic hematopoietic cell transplantation (HCT) from HLA haplotype–incompatible donors possible. In a setting of PTCy and tacrolimus/mycophenolate mofetil (MMF) as a graft-versus-host disease (GVHD) prophylaxis, a peripheral blood (PB) graft source as compared with bone marrow reduces the relapse rate but increases acute GVHD (aGVHD) and chronic GVHD (cGVHD). This phase 2 trial assessed sirolimus and MMF efficacy following PTCy as a GVHD prophylaxis after PB haploidentical HCT (haplo-HCT). With 32 evaluable patients (≥18 years) enrolled, this study had 90% power to demonstrate a reduction in 100-day grade II-IV aGVHD to 20% from the historical benchmark of 40% after haplo-HCT using PTCy/tacrolimus/MMF. At a median follow-up of 16.1 months, the primary end point of the trial was met with a day-100 grade II-IV aGVHD cumulative incidence of 18.8% (95% confidence interval [CI], 7.5% to 34.0%). There were no graft-failure events and the 1-year probability of National Institutes of Health (NIH) moderate/severe cGVHD was 18.8% (95% CI, 7.4% to 34.0%), nonrelapse mortality was 18.8% (95% CI, 7.4% to 34.0%), relapse was 22.2% (95% CI, 9.6% to 38.2%), disease-free survival was 59.0% (95% CI, 44.1% to 79.0%), GVHD-free relapse-free survival was 49.6% (95% CI, 34.9% to 70.5%), and overall survival was 71.7% (95% CI, 57.7% to 89.2%) for the entire cohort. These data demonstrate that GVHD prophylaxis with sirolimus/MMF following PTCy effectively prevents grade II-IV aGVHD after PB haplo-HCT, warranting prospective comparison of sirolimus vs tacrolimus in combination with MMF following PTCy as GVHD prophylaxis after PB HCT. This trial was registered at www.clinicaltrials.gov as #NCT03018223.